Perioperative Outcomes of Hyperlactatemia during Craniotomy: A Systematic Review and Meta-Analysis of 1,832 Patients - Mahfouz M. Sharapi; Nada M. Al-dardery; Mohamed A. El-Samahy; Amany E. Mahfouz; Ahmed S. Aljabali; Hazem S. Ghaith (Journal of Neuroanaesthesiology and Critical Care, 2023)
Background Hyperlactatemia, is common in patients undergoing neurosurgical procedures. Several studies have identified potential risk factors for developing hyperlactatemia in neurosurgical patients, including body mass index, surgery duration, tumour volume, and certain drugs such as volatile anesthetic agents and corticosteroids. This systematic review and meta-analysis examined the evidence of the association between perioperative lactate levels in patients undergoing brain surgery and postoperative morbidity and mortality.